2005
DOI: 10.1073/pnas.0502467102
|View full text |Cite
|
Sign up to set email alerts
|

Distinct role of lymphocyte function-associated antigen-1 in mediating effective cytolytic activity by cytotoxic T lymphocytes

Abstract: Lymphocyte function-associated antigen-1 (LFA-1) interaction with intercellular adhesion molecules (ICAMs) facilitates T cell antigen receptor (TCR)-mediated killing. To dissect TCR and LFA-1 contributions, we evaluated cytolytic activity and granule release by cytotoxic T lymphocytes (CTL) as well as intracellular granule redistribution and morphology of CTL stimulated with natural TCR ligand in the presence or absence of LFA-1 engagement. Although other adhesion mechanisms, e.g., CD2-CD58 interaction, could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
155
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(170 citation statements)
references
References 47 publications
14
155
0
Order By: Relevance
“…3F is due to the LFA-1-dependent properties of the immunological synapse. This loss of restriction is reminiscent of the diminution of CTL cytotoxicity with impaired focusing of CTL lytic granules onto target cells following disruption of the peripheral SMAC by LFA-1 blocking antibodies (14).…”
Section: Resultsmentioning
confidence: 99%
“…3F is due to the LFA-1-dependent properties of the immunological synapse. This loss of restriction is reminiscent of the diminution of CTL cytotoxicity with impaired focusing of CTL lytic granules onto target cells following disruption of the peripheral SMAC by LFA-1 blocking antibodies (14).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, although TCR engagement is necessary for inducing the cytotoxic activity of specific CD8 + T lymphocytes, integrins, mainly LFA-1 (a L b 2 ), play a crucial role in triggering CTL effector functions. It is now well established that the interaction of LFA-1 with its ligand ICAM-1 is necessary for effective target cell lysis by the released granules (2). CD103 (a E b 7 ) integrin also plays a pivotal role in epithelial target cell lysis by specific CD8 + T cells.…”
Section: Ytotoxic T Lymphocytes Play a Major Role In Antiviral Andmentioning
confidence: 99%
“…Adhesion molecules such as ICAM-1 and its receptors LFA-1 are crucial for immune synapse formation, antigen presentation 33) and lymphocyte killing. 34,35) It has been reported that adhesion defect in CD8+ T lymphocytes, which is caused by a combination of decreased cell surface levels of adhesion molecules, deficient LFA-1 activation, and the failure to recruit essential adhesion receptors to the membrane contact site formed with cognate target cells, weakens their capacity of cytolysis. 36) Therefore, EGCG-caused compromise of interaction between T lymphocytes and melanocytes will profoundly weaken the T lymphocyte activation and decrease the cytolysis of melanocytes by CD8+ CTL.…”
Section: Suppression Of T Lymphocyte Adhesion To Melanocytes By Egcgmentioning
confidence: 99%